Optimizing the Performance of State Security Intelligence of Temanggung Police Against Radicalism to Realize Community Security and Order in Temanggung Police - Hizkia Reinhard Hehamahwa (Akademi Kepolisian Republik Indonesia, 2023)
This research aims to obtain an overview of the role of performance that has been carried out by The Temanggung Police Intelligence Unit, especially in preventing disturbances caused by community organizations. In addition, an overview of how the implementation of prevention and what faktors influence it. In writing this research, the researcher uses management theory and organizational resources theory as a means for researchers to analyse and process data obtained when conducting research, as well as several concepts and understandings to clarify understanding related to this writing. The data was collected by using a qualitative approach, a field research using observation techniques, interviews with sources, and document review and data triangulation as a means of validating the data obtained. Based on the results of research that has been carried out, the implementation of patrols in the jurisdiction of the Temanggung Police Station is still far from expectations because the expected real change is a significant reduction in the number of disturbances to security and social order by mass organizations. In addition, the increase in state security unit has not gone well because it still cannot meet the indicators of the effectiveness of an activity, namely understanding the program, achieving goals, and real changes. It can be concluded that the role of state security Unit in improving early detection is still not maximized based on the theory and analytical methods used by researchers and also the faktors that influence it, especially in the internal scope of human resources and the methods used in the planning, implementation, as well as supervision and control stages.